(untitled) (Journal of Laboratory Animal Science, 2022)
Training is an important prerequisite to work with laboratory animals in vivarium facilities. Several organizations emphasize mandatory training prior to use of animals either for experiment or husbandry practices in order to meet organizational goals and core values especially in laboratory animal research facilities. The animal care personnel (ACP), animal care supervisors (ACS), scientists, study director, investigators and veterinarians should be trained in their relevant field to perform procedures based on the kind of work they handle on day to day animal care and experimental activities. Any institution can formulate a formal training program considering their requirements and species housed within the facility. Syngene laboratory Animal Research (SLAR) has been the premier organization who explicitly support for training and development of staff at all levels with commitment to increase skill levels of team members to deliver high quality animal care on par with global standards. The noteworthy training matrix of ALAT, LAT, LATG, and FELASA “C” level certification was cleared by at least 8 and 14 staff, respectively, that includes ACS/investigators/veterinarians apart from specialized techniques on animal procedures. The training, certification and continuing professional development (CPD) showed competency among staff with improved supervisory skills and managerial performance especially animal husbandry as well as other experimental procedures. A viable option of cross-training also provided to carryout weekend animal care including critical functions during emergency situations as redundant backups such a way to maintain the well being of animals without any compromise. Dissemination of knowledge and effective communication with transparency is an essential component for successful training outcomes and practical applications at the laboratories. Collectively, the facility veterinarians and quality assurance have been ensuring the periodical training and monitoring oversight of all the activities in vivarium.